2013
DOI: 10.3144/expresspolymlett.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Improving the thermal conductivity of epoxy resin by the addition of a mixture of graphite nanoplatelets and silicon carbide microparticles

Abstract: Graphene nanosheet (GNS), a single layer of hexagonally arrayed sp 2 -bonded carbon, has attracted increasing attention recently due to its excellent thermal, electrical and mechanical properties. However, manufacturing GNS-filled composites has been very challenging due to the difficulties in large-scale production of GNSs and their dispersion in matrices. GNSs tend to form irreversible agglomerates or even restack to form graphite through van der Waals interactions during the processing of bulk-quantity GNSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…It is observed that heat conductivity first increases linearly with the degree of agglomeration, reaches a maximum at the percolation threshold and finally decreases. The raising of conductivity with size (at nanoscale) was confirmed by many authors [46][47][48][49][50][51] in the case of epoxy resin with various fillers and by Prasher et al [31,52] in the case of nanofluids.…”
Section: Final Validation Of Dependence Of the Effective Thermal Condsupporting
confidence: 51%
“…It is observed that heat conductivity first increases linearly with the degree of agglomeration, reaches a maximum at the percolation threshold and finally decreases. The raising of conductivity with size (at nanoscale) was confirmed by many authors [46][47][48][49][50][51] in the case of epoxy resin with various fillers and by Prasher et al [31,52] in the case of nanofluids.…”
Section: Final Validation Of Dependence Of the Effective Thermal Condsupporting
confidence: 51%
“…Thermal conductivity as well as other thermal properties depend on properties of both the additives and the matrix [17,35]. At low wt%, the fillers in LLDPE are in isolated states.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Carbon based fillers have been used to successfully improve the thermal performance of the PCM itself [20] and resins [21]. Results show that with the addition of 7 wt% of carbon fibres to PCM, the thermal conductivity can be quadruplicated [22] while the addition of 71.7 wt% of silicon carbide to epoxy can improve its thermal conductivity by 20 times [23].…”
Section: Introductionmentioning
confidence: 99%